Hiekkapohja hydrothermal system – ore mineral, lithogeochemical and paleomagnetic evidence from the Paleoproterozoic Central Finland Granitoid Complex - Heilimo Esa; Halonen Sini; Mertanen Satu; Niemi Sami; Mikkola Perttu (Geological Society of Finland, 2025)
The Paleoproterozoic Svecofennian Central Finland Granitoid Complex (CFGC) has been regarded as an area of low mineralisation potential. The Hiekkapohja area, 20km north-east of the town of Jyväskylä, host a concentration of variable metalliferous showings. Samples from mineralised boulders and outcrops display variable combinations of anomalously high concentrations of Cu, Mo, Zn, Pb, W, Pb, Ag, As, and Au. The area is composed mainly of peraluminous and ferroan granitoids. The dominant porphyritic Hiekkapohja granodiorite (~1.88 Ga) is cross-cut by the equigranular Soimavuori granite of similar age. The porphyritic Lehesvuori granite on the western side of the study area represents marginally older (~1.89 Ga) magmatism. The paragenetic sequence of the ore minerals shows that the Hiekkapohja area has been affected by at least two separate stages of hydrothermal activity. The first mineralisation stage was widespread, crystallising typically chalcopyrite, pyrrhotite, sphalerite, galena, arsenopyrite, magnetite and Ag-bearing minerals. After the first stage, a low temperature oxidising phase formed hematite and marcasite. The second mineralisation stage enclosed low temperature minerals, such as marcasite and native Ag and Ag-minerals, as inclusions inside chalcopyrite, pyrite, pyrrhotite, sphalerite, and arsenopyrite. The mineralised samples typically display signs of K-metasomatism and less commonly signs of propylitic alteration. During the second mineralisation stage the fluid flow was controlled by the dominant 120°–135° trending shear zones. Both the hydrothermal activity and the regional geology indicate that porphyry type ore forming processes have occurred in the Hiekkapohja area. Paleoproterozoic resetting of the remanent magnetisation is further evidence for the role of the hydrothermal system.